THE EFFECT OF GEOGEBRA-ASSISTED DIRECT INSTRUCTION ON STUDENTS' SELF-EFFICACY AND SELF-REGULATION - Zetriuslita Zetriuslita; Nofriyandi Nofriyandi; Endang Istikomah (Jurnal Infinity, 2020)
This study aims to find out the effect of Geogebra Assisted Direct Instruction on students' self-efficacy and self-regulation.  This is a mixed method research with a sequential explanatory strategy, while the research design is a pretest and posttest unequivalent group design.  The experimental group applied Geogebra Assisted Direct Instruction while the control group used conventional learning.  The population in this study is the third semester students who have studied Field and Space Analytic Geometry.  The research sample was selected using cluster random sampling technique.  The research instruments were self-efficacy and self-regulation questionnaires for quantitative data and interview sheets for qualitative data.  Data analysis was performed quantitatively using inferential statistical analysis and qualitatively analyzing the results of interview with students.  The results showed that there was a significant effect of geogebra-assisted direct instruction on the achievement of students' self-efficacy and self-regulation.  From the interviews it was found that the application of Geogebra-assisted Direct Instruction can facilitate the achievement of students' self-efficacy and self-regulation.